Traditional Meditation and Yoga Exercises as an Alternative Therapy for Insomnia - Putu Setiani; Agung Setiabudi; I Nyoman Gede Semarajana; Kadek Ayu Meilinda Dusak; Kadek Ayu Savitri Mahadewi (Green Publisher Indonesia, 2025)
Insomnia is a sleep disorder that affects a person's quality of life, lowers daily performance, and is even associated with long-term health problems such as depression, anxiety, and heart problems. Nowadays, many individuals are looking for non-drug alternatives to overcome insomnia. One of the increasingly popular approaches is yoga and meditation. This study aims to find out the relationship between yoga practice and meditation on insomnia. A prospective cohort study in the population of DHSP Bali who experienced insomnia with an age range of 18–80 years during the period April to July 2025. The average age of the sample was 49.71 years (SD±12.95) (p = 0.084) with 16 males (57.1%) and 12 females (42.9%). The average ISI score before meditation and yoga was 15.21 (SD±4.55) (p = 0.090) and the ISI score after meditation and yoga was 12.14 (SD±4.56) (p = 0.067). There was an average mean difference of 3.071 points between the ISI scores before and after yoga and meditation practice for 3 consecutive months. An improvement in the average ISI score before and after intensive yoga and meditation practice twice every week for 3 months was shown to improve insomnia complaints. Regular yoga-meditation practice demonstrates statistically significant efficacy in reducing insomnia severity through mechanisms including parasympathetic activation, increased GABA levels, and positive neuroplastic changes in the prefrontal cortex and hippocampus, providing evidence-based support for integrative non-pharmacological insomnia management.